Consumer Knowledge and Perception in Purchasing Decisions for East Belitung Teran Honey - Juhari Juhari; Abdul Rachim (International Journal of Magistravitae Management, 2023)
As a region that produces a significant amount of Heterotrigona Itama honey, the Local Government of East Belitung Regency encourages this honey to become one of the region’s flagship products. In line with this goal, this study was conducted to understand and analyze consumer knowledge and perception regarding purchasing decisions for East Belitung Teran Honey. The findings aim to enable the local government to effectively implement appropriate marketing policies and promote East Belitung Teran Honey. The research methodology involved distributing questionnaires through face-to-face interviews and via Google Forms. The study’s respondents comprised 100 consumers of Forest Honey and East Belitung Teran Honey. The results of this study indicate that consumer knowledge does not significantly influence the purchasing decision for East Belitung Teran Honey. However, it revealed that consumer perception positively and significantly impacts the purchasing decision for East Belitung Teran Honey.